Resting-State Functional MRI in Dyslexia: A Systematic Review - Bruce Martins; Isabel A. B. Verrone; Mariana M. I. Sakamoto; Mariana Y. Baba; Melissa E. Yvata; Katerina Lukasova; Mariana P. Nucci (Biomedicines)
Background/Objectives: The present review addresses and systematically analyses the most frequently reported neuropsychological and functional connectivity (FC) alterations in individuals with dyslexia compared to controls. By synthesizing extant evidence, this work aims to clarify dyslexic connectivity profiles and provide a foundation for future research and clinical translation. Methods: This systematic review analyzed publications from the last 10 years in two scientific databases, focusing on individuals with dyslexia, without previous injuries, who underwent resting-state functional magnetic resonance imaging (rs-fMRI) assessments, comparing them with typical readers. Results: This review revealed that most dyslexia studies on brain FC using rs-fMRI focused on children (92%), underscoring a gap in research on adults and limiting our understanding of brain maturation processes and neuroplasticity across the lifespan. FC alterations primarily involved ipsilateral connections (60%), with reduced connectivity mainly in the left hemisphere (40%), particularly in posterior regions, aligning with the neurobiological hypothesis of phonological and visual–phonological dysfunctions in dyslexia. Conversely, increased connectivity in the right hemisphere (20%) may indicate the engagement of an alternative network and highlight the complexity of neural adaptations in dyslexia. Conclusions: The findings highlight a significant gap in the study of adult dyslexia and suggest that FC alterations predominantly affect the left hemisphere, with possible compensatory mechanisms in the right hemisphere. Reading fluency improvements in dyslexia may be linked to connectivity changes across multiple brain networks rather than the classical reading circuitry alone. Increased and decreased connectivity in various regions related to executive function, language, and salience processing indicate that broader cognitive mechanisms play a key role in reading performance.